(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
The rate of indirect photon-electron conversion for scintillator materials coupled with arrays of photodiodes is at least 25 times smaller than the rate of direct conversion. We examine the conditions to be fulfilled by semiconductors undergoing such direct conversion to be applied to X-ray imaging. Bulk grown materials are not well-suited to this application because large defect concentrations give rise to strongly non-uniform electronic properties. We argue that epitaxial layers are suitable for use as imaging devices and we illustrate our argument using the case of thin epitaxial GaAs layers. Detectors made with such layers exhibit a good energy resolution, and a charge collection efficiency which approaches one. إن نسبة التحويل غير المباشر لـ "فوتون – الكترون" في المواد الوميضية – المقرونة بترتيب معين لثنائيات ضوئية أقل بحوالي 25 مرة من نسبة التحويل المباشر. وسوف نتفحص الشروط التي يجب أن تتوفر في أنصاف النواقل عند خضوعها لظاهرة التحويل المباشر، وذلك عند استخدامها للتصوير بواسطة أشعة x. إن الصفائح المتوفرة من المركب Ga-As غير ملائمة لهذا النوع من التطبيقات، بسبب ارتفاع كثافة العيوب التي تؤدي إلى عدم انتظام في خواصها الالكترونية. وسوف نحاول أن نبرهن على أن الكواشف، من نوع Ga-As التي تعتمد صناعتها على تقنية التنضيد، أي توضع الطبقات فوق بعضها البعض بالتبخر هي الطريقة الوحيدة الملائمة للاستخدام في أجهزة التصوير بأشعة X، وسندعم حجتنا هذه باستخدام طبقات رقيقة من المركب Ga-As. وتظهر الكواشف المصنعة من مثل هذه الطبقات الرقيقة ميز عالي للطاقة، ومردود وتجميع شحنة فعلية قريب من الواحد.